(untitled) (Biological Sciences - PJSIR, 2010)
The effect of market storage methods in Nigeria on the antioxidant properties of Telfairia occidentalis was assessed over a period of 96 hours with respect to the vitamin C, total phenol and phytate contents, as typified by their reducing power and free scavenging ability. T. occidentalis had a phytate content of 28.83 mg/100 g and there was no significant (P>0.05) difference in the phytate content in the first 24 h of storage but significantly (P>0.05) reduced at the end of the storage period of 96 h (26.74 mg/100 g) with 7.24% loss. Vitamin C content reduced significantly (P>0.05) as the storage period increased with a very high percentage loss (81.58%) at the end of the storage period. The vegetable had 2.78 mg GAE/100 g total phenol and was slightly reduced but not significant (P>0.05) during the first 24 h of storage. T. occidentalis had scavenging ability > 90%, which significantly (P>0.05) decreased as the storage period increased (57.47% loss at 100% conc. and 56.28 % loss at 50% conc.).